Delay and trace fear conditioning in a complex virtual learning environment—neural substrates of extinction - Ewald, Heike; Glotzbach-Schoon, Evelyn; Gerdes, Antje B. M.; Andreatta, Marta; Müller, Mathias; Mühlberger, Andreas; Pauli, Paul (Frontiers in Human Neuroscience, 2014)
Extinction is an important mechanism to inhibit initially acquired fear responses. There is growing evidence that the ventromedial prefrontal cortex (vmPFC) inhibits the amygdala and therefore plays an important role in the extinction of delay fear conditioning. To our knowledge, there is no evidence on the role of the prefrontal cortex in the extinction of trace conditioning up to now. Thus, we compared brain structures involved in the extinction of human delay and trace fear conditioning in a between-subjects-design in an fMRI study. Participants were passively guided through a virtual environment during learning and extinction of conditioned fear. Two different lights served as conditioned stimuli (CS); as unconditioned stimulus (US) a mildly painful electric stimulus was delivered. In the delay conditioning group (DCG) the US was administered with offset of one light (CS+), whereas in the trace conditioning group (TCG) the US was presented 4s after CS+ offset. Both groups showed insular and striatal activation during early extinction, but differed in their prefrontal activation. The vmPFC was mainly activated in the DCG, whereas the TCG showed activation of the dorsolateral prefrontal cortex (dlPFC) during extinction. These results point to different extinction processes in delay and trace conditioning. VmPFC activation during extinction of delay conditioning might reflect the inhibition of the fear response. In contrast, dlPFC activation during extinction of trace conditioning may reflect modulation of working memory processes which are involved in bridging the trace interval and hold information in short term memory.